A Gain-of-Function Mutation in the Ca2+ Channel ORAI1 Causes Stormorken Syndrome with Tubular Aggregates in Mice - Laura Pérez-Guàrdia; Emma Lafabrie; Nadège Diedhiou; Coralie Spiegelhalter; Jocelyn Laporte; Johann Böhm (Cells, 2024)
Store-operated Ca2+ entry (SOCE) controls Ca2+ homeostasis and mediates multiple Ca2+-dependent signaling pathways and cellular processes. It relies on the concerted activity of the reticular Ca2+ sensor STIM1 and the plasma membrane Ca2+ channel ORAI1. STIM1 and ORAI1 gain-of-function (GoF) mutations induce SOCE overactivity and excessive Ca2+ influx, leading to tubular aggregate myopathy (TAM) and Stormorken syndrome (STRMK), two overlapping disorders characterized by muscle weakness and a variable occurrence of multi-systemic anomalies affecting spleen, skin, and platelets. To date, different STIM1 mouse models exist, but only a single ORAI1 mouse model with muscle-specific TAM/STRMK phenotype has been described, precluding a comparative analysis of the physiopathology in all affected tissues. Here, we generated and characterized mice harboring a prevalent ORAI1 TAM/STRMK mutation and we provide phenotypic, physiological, biochemical, and functional data. Examination of Orai1V109M/+ mice revealed smaller size, spleen enlargement, reduced muscle force, and decreased platelet numbers. Morphological analyses of muscle sections evidenced the presence of tubular aggregates, the histopathological hallmark on biopsies from TAM/STRMK patients absent in all reported STIM1 models. Overall, Orai1V109M/+ mice reliably recapitulate the human disorder and highlight the primary physiological defects caused by ORAI1 gain-of-function mutations. They also provide the possibility to investigate the formation of tubular aggregates and to develop a common therapy for different TAM/STRMK forms.